RANCANGAN JADWAL BUKA TUTUP OPERASI OTOMATIS BERBASIS ARDUINO UNO DI GERBANG CEWAMA ASRAMA CURUG 1 SEKOLAH TINGGI PENERBANGAN INDONESIA .pdf - Dena Farasi; KGS. M. Ismail; R.B. Budi Kartika W (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
In the Curug 1 ICAI Dormitory, there is a gate which connect between the main road and the dormitory. The gate is the main access for cadet to enter and exit the dormitory. The system work with Arduino 4 Input Microcontroller (2 analogs, 2 digitals), Real Time Clock module with CR2032 battery type and I2C Communication (SDA, SCL). Microcontroller will activate relay that capable to handle 220 volts of voltage and 10 Ampere of currents. Then Relay will give a cue to contactor and activate the Electric Motor as Prime Mover. The cable which used to connect RTC module to Arduino UNO is AWG cable 39 for 0.018 Ampere of Currents and AWG cable 11 for 12 Ampere of Currents to connect between Relay and Electric Motor. This following steps to program Arduino UNO : Activate the RTC module, Relay 1 and Relay 2 according to the specified time, download the DS3231 file, display the time planting program, and display the “current time”. With the application of the automation gate, it’s expected open-close gate automatically according to schedule which has specified.